Innovative water preparation technology for production of kombucha fermented beverage - Dulka, Olha; Prybylskyi, Vitalii; Oliynyk, Svitlana; Fedosov, Oleksii; Кuts, Anatolij; Sharan, Larisa; Koretska, Iryna; Tiurikova, Inna (My University, 2023)
The article presents the results of theoretical and experimental research on improvement of water preparation technology for non-alcoholic production of kombucha fermented drink. Complex action of the studied materials with adsorptioning, ion exchanging and redoxing properties provides the water conditioning, which allows improving the organoleptic indicators of the final product and increases its biological value. The expediency of using in the technology of preparation water for making kombucha drink has been established for clinoptilolite, rock crystal and activated carbon. While treating water from various sources with the proposed materials it’s overall softness and the total iron content were decreased, the content of biologically active substances in the final drink increased and organoleptic characteristics improved. The content of polyphenols substances in the final drink increased on the average 1.6 times compared to the untreated artesian water and the water from centralized water supply network. It was found that the high water hardness had a negative effect on the fermentation caused by the Medusomyces gisevii yeast culture and it made the organoleptic qualities of the final drink worse. The correlation between water indicators, wort fermentation dynamics and organoleptic evaluation of final drinks had been defined. The highest organoleptic values had been got by the samples of the drink prepared using water treated with clinoptilolite, activated carbon and rock crystal. У статті наведено результати теоретичних та експериментальних досліджень з удосконалення технології підготовки води для виробництва безалкогольного ферментованого напою комбуча. Комплексна дія досліджених матеріалів із адсорбційними, іонообмінними та окисно-відновними властивостями забезпечує кондиціювання води, що дозволяє покращити органолептичні показники готового продукту та підвищує його біологічну цінність. Встановлено доцільність використання клиноптилоліту, гірського кришталю та активованого вугілля у технології підготовки води для приготування комбучі. При обробці води з різних джерел запропонованими матеріалами зменшувалась її загальна жорсткість, вміст загального заліза, збільшувався вміст біологічно активних речовин в готовому напої, покращувались органолептичні характеристики. В готовому напої збільшувався вміст поліфенольних речовин в середньому у 1.6 рази у порівнянні з використанням необробленої води з артезіанської свердловини та централізованої мережі водопостачання. Встановлено, що висока жорсткість води негативно впливала на зброджування сусла культурою Medusomyces gisevii та погіршувала органолептичні якості готового напою. Визначено кореляцію між показниками води, динамікою бродіння сусла та органолептичною оцінкою готових напоїв. Найвищу органолептичну оцінку отримали зразки напою, що приготовлені з використанням води, обробленої послідовно клиноптилолітом, активованим вугіллям та гірським кришталем.
Keywords: вода; безалкогольні напої; комбуча; водопідготовка; клиноптилоліт; гірський кришталь; активоване вугілля; water; soft drinks; kombucha; water treatment; clinoptilolite; rock crystal; activated carbon; кафедра готельно-ресторанної справи; кафедра біотехнології продуктів бродіння і виноробства